THE USAGE OF KIT-FOR-KIDS IN DISCOVERY LEARNING MODEL TO IMPROVE THE UNDERSTANDING OF SCIENCE TEACHING MATERIALS ON ELEMENTARY SCHOOL STUDENTS - Sigit Setiawan; Andi Suhandi (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
This research was conducted to find out the increased in understanding of elementary school students' teaching material through the use of kits for kids on discovery learning models. This research used quasi-experimental method using the matching only pretest and posttest control group design. The learning process in the experimental group applies the discovery learning model with kit for kids while the control group applies traditional learning. Learning take place during two meetings, both in the experimental group and control group. Each learning process is conducted the observation process of the implementation of learning activities. The subjects in the experimental group were 23 students and in the control group were 22 students. The research instrument uses multiple choice tests. Data analysis techniques used n-gain mean data and U Mann-Whitney SPSS Version 22 non-parametric test. The results showed that the increase in understanding of teaching materials on students who received discovery learning model assisted with a kit-for-kid was higher than students who received traditional learning.Keywords: Discovery Learning; Understanding Teaching Material